PEMODELAN FAKTOR KEMISKINAN DI KOTA PADANG TAHUN 2021 MENGGUNAKAN REGRESI SPASIAL - Putri, Mila Alfikas; Ramadhan, Risky (JURNAL BUANA, 2024)
Abstract Based on a survey conducted by BPS, it is known that in West Sumatra province the city with the highest poverty rate is the city of Padang. Poverty in Padang City experienced an increase in 2021 and then decreased in 2022. To see the relationship between factors that influence poverty in Padang City, the spatial regression method was used by paying attention to spatial dependence. This research aims to determine several factors that can influence poverty in Padang City. The results of the research show that the factors that can influence poverty in Padang City in each sub-district are the number of public health service facilities (X1), the distance of the sub-district from the city center (X3), and population density (X4).